Inovação aberta e crowdsourcing : um estudo de caso de PMEs do Polo Estadual da Indústria de Jóias e Lingeries, Guaporé-RS - Dalamaria, Bárbara Adelle (2025)
Open innovation is an approach linked to business management that focuses on developing innovative projects through the assistance of external partnerships, which can be characterized as other organizations, government, academic researchers, universities, among other stakeholders. In turn, crowdsourcing can be characterized in Administration studies as an open innovation practice that makes it possible to use the knowledge of the crowd through digital platforms in order to qualify processes and products. Both practices can be incorporated from a perspective of complementarity in small and medium-sized enterprises (SMEs), with the figure of the entrepreneur/manager as a central element in decision-making, providing subsidies so that resource limitations are mitigated. However, even though they are beneficial for SMEs, there are limiting elements for the adoption of these practices. Therefore, the challenge of this study was to understand how open innovation and crowdsourcing are configured in the context of SMEs in the State Jewelry and Lingerie Industry Hub, Guaporé/RS. Aiming to anchor the theoretical constructs that supported the study, the theoretical framework presented the concepts of open innovation, crowdsourcing and entrepreneurship with a focus on SMEs. After articulating the presented theory, it was possible to develop propositions and a theoretical research model with the aim of illustrating the considerations found regarding the relationship between the themes addressed. The methodological procedures of the study followed an exploratory qualitative approach with the aim of deeply understanding the context of the organizations studied. Data collection was carried out through an instrument developed from the analyzed bibliography, validated with experts and applied in interviews with open-ended questions structured with the managers of the participating companies and stakeholders participating in the innovation ecosystem. The results demonstrate that segments of the industry, such as metalworking, adopt open innovation and co-creation practices with other companies with less resistance. On the other hand, the companies in the textile, notebook and jewelry sectors analyzed still have difficulty implementing these practices. Finally, the companies analyzed have the resources to implement open innovation and crowdsourcing actions, as do SMEs analyzed in other contexts. However, they are limited by the lack of participation in innovation ecosystems, the lack of public policies to encourage entrepreneurial activity and digitalization, and the local context and culture. This transforms these factors into barriers with the potential to repress open innovation. The theoretical contributions of this study are characterized by the approach to the concepts presented from a new context. The practical contributions translate into the evaluation of limiting elements for the adoption of such practices in the context analyzed.